Certain Issues Of Protecting The Rights Of Absent Heirs In Inheritance Law (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes current issues of protecting the rights of absent heirs in inheritance law. The author thoroughly examined the necessity of preserving inheritance property after the opening of inheritance and the legal problems arising in this process. The research highlights practical difficulties through studying the role of notaries in preserving inheritance property, its inventory, and ensuring the interests of heirs. Special cases such as heirs with unknown place of residence, unborn heirs, and enterprise inheritance are particularly examined. The article conducts a comparative analysis with foreign experience, particularly with US inheritance law. By comparing the legislation of the Russian Federation with the norms of the Civil Code of Uzbekistan, ways for more effective protection of absent heirs' rights are proposed. In conclusion, the author presented specific proposals for necessary additions to the legislation